Influence of connection type on the biomechanical behavior of distal extension mandibular removable partial dentures supported by implants and natural teeth. Issue 3 (17th February 2016) - Xiao, Wei; Li, Zhiyong; Shen, Shiqian; Chen, Shaowu; Chen, Sulin; Wang, Jiawei
Abstract : Few studies are performed to evaluate the influence of connection type on the stress distribution of distal extension mandibular removable partial dentures (RPDs) supported by both implants and natural teeth. In this study, five three-dimensional finite element models were prepared to simulate mandibular bilateral partially edentulous arches. Four were RPDs supported by both implants and natural teeth, and the other one was RPDs supported only by natural teeth. The maximum equivalent (EQV) stress values of bone around implants, the abutments, and the mucosa displacements of the related supporting structures were measured. It was found that a non-rigid telescopic coping was more favorable to protect the implant than a rigid telescopic coping. Compared with other connection types, the easy resilient attachment (ERA) system seemed to be effective to associate implant without complications. However, the results obtained in the present study should be cautiously interpreted in the clinic.